"The support has been brilliant": experiences of Aboriginal and Torres Strait Islander patients attending two high performing cancer services - Emma V. Taylor; Marilyn Lyford; Michele Holloway; Lorraine Parsons; Toni Mason; Sabe Sabesan; Sandra C. Thompson (BMC, 2021)
Abstract Background Improving health outcomes for Indigenous people by providing person-centred, culturally safe care is a crucial challenge for the health sector, both in Australia and internationally. Many cancer providers and support services are committed to providing high quality care, yet struggle with providing accessible, culturally safe cancer care to Indigenous Australians. Two Australian cancer services, one urban and one regional, were identified as particularly focused on providing culturally safe cancer care for Indigenous cancer patients and their families. The article explores the experiences of Indigenous cancer patients and their families within the cancer services and ascertains how their experiences of care matches with the cancer services' strategies to improve care. Methods Services were identified as part of a national study designed to identify and assess innovative services for Indigenous cancer patients and their families. Case studies were conducted with a small number of identified services. In-depth interviews were conducted with Indigenous people affected by cancer and hospital staff. The interviews from two services, which stood out as particularly high performing, were analysed through the lens of the patient experience. Results Eight Indigenous people affected by cancer and 23 hospital staff (Indigenous and non-Indigenous) were interviewed. Three experiences were shared by the majority of Indigenous cancer patients and family members interviewed in this study: a positive experience while receiving treatment at the cancer service; a challenging time between receiving diagnosis and reaching the cancer centre; and the importance of family support, while acknowledging the burden on family and carers. Conclusions This article is significant because it demonstrates that with a culturally appropriate and person-centred approach, involving patients, family members, Indigenous and non-Indigenous staff, it is possible for Indigenous people to have positive experiences of cancer care in mainstream, tertiary health services. If we are to improve health outcomes for Indigenous people it is vital more cancer services and hospitals follow the lead of these two services and make a sustained and ongoing commitment to strengthening the cultural safety of their service.